A comparative study of populations of Ectopleura crocea and Ectopleura ralphi (Hydrozoa, Tubulariidae) from the Southwestern Atlantic Ocean - Antunes Imazu, Mauricio (2014)
Ectopleura crocea (L. Agassiz, 1862) and Ectopleura ralphi (Bale, 1884) are two of the nominal tubulariid species re-corded for the Southwestern Atlantic Ocean (SWAO), presumably with wide but disjunct geographical ranges and similar morphologies. Our goal is to bring together data from morphology, histology, morphometry, cnidome, and molecules (COI and ITS1+5.8S) to assess the taxonomic identity of two populations of these nominal species in the SWAO. We have ob-served no significant difference or distributional patterns between the so-called Brazilian E. ralphi and Argentine E. cro-cea for both morphological and molecular data. Therefore, SWAO populations of Ectopleura belong to the same species. In a broader view, it is difficult to find decisive character distinguishing E. crocea from E. ralphi, and both species have indeed recently been synonymized, with the binomen E. crocea having nomenclatural priority. Geographically broader genetic analysis should be carried out in order to test the validity of this synonymy because taxonomical procedures such as studying type specimens and documenting broad phenotypic variability have not yet been conducted.